2010
DOI: 10.1093/mutage/geq031
|View full text |Cite
|
Sign up to set email alerts
|

DNA repair and the origins of urinary oxidized 2'-deoxyribonucleosides

Abstract: Monitoring oxidative stress in vivo is made easier by the ability to use samples obtained non-invasively, such as urine. The analysis of DNA oxidation, by measurement of oxidized 2'-deoxyribonucleosides in urine, particularly 8-oxo-7,8-dihydro-2'-deoxyguanosine (8-oxodG), has been reported extensively in the literature in many situations relating to various pathologies, populations and environmental exposures. Understanding the origins of urinary 8-oxodG, other than it simply being a marker of DNA oxidation or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
63
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(64 citation statements)
references
References 118 publications
1
63
0
Order By: Relevance
“…The function of BRCA1 in DNA repair includes homologous recombination, but it also has multiple functions in the cellular response to DNA damage, including contributing to the recruitment of BRCA2. The main repair pathway of oxidized DNA lesions in all cells, from E. coli to human, is base excision repair (BER) [7, 8]. The understanding of breast carcinogenesis in the context of BRCA1- or BRCA2-deficiency suggests that both proteins play a role in the repair of oxidative DNA damage, but not via BER.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The function of BRCA1 in DNA repair includes homologous recombination, but it also has multiple functions in the cellular response to DNA damage, including contributing to the recruitment of BRCA2. The main repair pathway of oxidized DNA lesions in all cells, from E. coli to human, is base excision repair (BER) [7, 8]. The understanding of breast carcinogenesis in the context of BRCA1- or BRCA2-deficiency suggests that both proteins play a role in the repair of oxidative DNA damage, but not via BER.…”
Section: Discussionmentioning
confidence: 99%
“…Base excision repair (BER) is the main pathway to repair oxidized DNA lesions in all cells, conserved from E. coli to humans [7, 8]. BER genes are essential in mouse embryonic development, providing housekeeping function for endogenous metabolism that produces oxidative DNA damage.…”
Section: Introductionmentioning
confidence: 99%
“…Urinary 8-oxodG in steady state reflects products of DNA damage and repair (35), and could also be regarded as biomarkers of oxidative stress in occupational or environmental fields (6-10). Our results also showed that traffic conductors could have higher levels of urinary 8-oxodG than indoor office workers, which were in agreement with previous studies (7,9).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the highly reactive species peroxynitrite, formed by the near-diffusion limited reaction between nitric oxide and superoxide anion, may also directly oxidize proteins or nitrate tyrosine residues leading to nitrosative stress. Additionally, the formation of 8-oxo-7,8-dihydro-2′-deoxyguanosine (8-oxodG), 2′ a marker of DNA oxidation, was demonstrated to induce mutagenic changes aside from interfering with gene expression (19)(20)(21)(22).…”
Section: Study Design and Patientsmentioning
confidence: 99%